Inter- and intra-species intercropping of barley cultivars and legume species, as affected by soil phosphorus availability - Darch, Tegan; Giles, Courtney D.; Blackwell, Martin S. A.; George, Timothy S.; Brown, Lawrie K.; Menezes-Blackburn, Daniel; Shand, Charles A.; Stutter, Marc I.; Lumsdon, David G.; Mezeli, Malika M.; Wendler, Renate; Zhang, Hao; et al. (Plant and soil, 2018)
Aims Intercropping can improve plant yields and soil phosphorus (P) use efficiency. This study compares inter- and intra-species intercropping, and determines whether P uptake and shoot biomass accumulation in intercrops are affected by soil P availability. Methods Four barley cultivars (Hordeum vulgare L.) and three legume species (Trifolium subterreneum, Ornithopus sativus and Medicago truncatula) were selected on the basis of their contrasting root exudation and morphological responses to P deficiency. Monocultures and barley-barley and barley-legume intercrops were grown for 6 weeks in a pot trial at very limiting, slightly limiting and excess available soil P. Aboveground biomass and shoot P were measured. Results Barley-legume intercrops had 10–70% greater P accumulation and 0–40% greater biomass than monocultures, with the greatest gains occurring at or below the sub-critical P requirement for barley. No benefit of barley-barley intercropping was observed. The plant combination had no significant effect on biomass and P uptake observed in intercropped treatments. Conclusions Barley-legume intercropping shows promise for sustainable production systems, especially at low soil P. Gains in biomass and P uptake come from inter- rather than intra-species intercropping, indicating that plant diversity resulted in decreased competition between plants for P.